11th International Energy Conversion Engineering Conference 2013
DOI: 10.2514/6.2013-3928
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Efficiency Segmented Thermoelectric Couples

Abstract: = maximum couple thermal-to-electric conversion efficiency GPHS-RTG = General Purpose Heat Source Radioisotope Thermoelectric Generator MMRTG = Multi-mission Radioisotope Thermoelectric Generator RTG = radioisotope thermoelectric generator T H = hot junction temperature T C = cold junction temperature T avg = average couple temperature Z = thermoelectric figure of merit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…26,27 Significant progress has been made on improving and developing new thermoelectric materials in recent years, however actual device demonstrations have been scarce and are mostly motivated by waste heat recovery applications. [28][29][30][31][32][33][34] The auxiliary efficiency in Eq. (1) accounts for possible system parasitic losses such as electricity consumption for pumping and cooling.…”
Section: Csteg Efficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…26,27 Significant progress has been made on improving and developing new thermoelectric materials in recent years, however actual device demonstrations have been scarce and are mostly motivated by waste heat recovery applications. [28][29][30][31][32][33][34] The auxiliary efficiency in Eq. (1) accounts for possible system parasitic losses such as electricity consumption for pumping and cooling.…”
Section: Csteg Efficiencymentioning
confidence: 99%
“…Thermoelectric materials typically perform best in a relatively narrow temperature range. 11,27,31,33,39 Modeling has shown that higher performance can be achieved by segmenting thermoelectric legs with different materials permitting large operating temperature differences. 11,39 For example, by using a low-temperature material such as bismuth telluride operating up to ~250 °C and a high-temperature material such as skutterudite operating above ~250 °C, a CSTEG can theoretically achieve an efficiency of over 10%.…”
Section: Csteg Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional thermoelectric device manufacturing comprises of labour-intensive methodology including soldering, brazing and adhesive bonding [4] which are limited by the thermal stability (as the braze melting temperature is normally its re-melting temperature) and the extensive growth of reaction layers at the thermoelectric–interconnect interfaces, causing mechanical or electrical deterioration of the entire assembly. In the conventional skutterudite devices, metal interconnects are joined to the metallized semiconductor elements to provide permanent interconnection either by the mechanical (i.e., using compression springs [5]) or chemical (i.e., solid-state diffusion bonding [6,7] or brazing [8]) methods of joining. Designing a suitable metallization and bonding technique for the skutterudite family of compounds is particularly difficult with the complex reactivity of their individual components, since antimony (Sb) can react with most of the transition metals to form brittle antimonide intermetallic compounds (IMCs).…”
Section: Introductionmentioning
confidence: 99%